2013
DOI: 10.1080/19443994.2013.781001
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in flow and water quality measurement data: A case study in the Daning River watershed in the Three Gorges Reservoir region, China

Abstract: A B S T R A C TMeasurement data are used to calibrate and validate the effect of models. In this study, four types of uncertainty categories covering flow measurement, sample collection, sample preservation/storage and laboratory analysis were quantified for flow, sediment and water quality measurement data under best-, typical-and worst-case scenarios. The root mean square error propagation method was used to calculate the overall uncertainty. A case study was conducted in the Daning River with the Soil and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Some results showed that spatial interpolation techniques resulted in considerable uncertainty of rainfall spatial variability and transferred larger uncertainty to H/NPS modelling. In addition, Shen et al (2013)'s study has been carried out into the effect of GIS data on water quality modelling and the uncertainty related to the combination of the available GIS maps. All these kinds of prediction uncertainty relating to limited model structures, or model input data, could result in discrete variables.…”
Section: The Mca Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some results showed that spatial interpolation techniques resulted in considerable uncertainty of rainfall spatial variability and transferred larger uncertainty to H/NPS modelling. In addition, Shen et al (2013)'s study has been carried out into the effect of GIS data on water quality modelling and the uncertainty related to the combination of the available GIS maps. All these kinds of prediction uncertainty relating to limited model structures, or model input data, could result in discrete variables.…”
Section: The Mca Methodsmentioning
confidence: 99%
“…To incorporate this type of uncertainty, MCA was implemented using the Monte Carlo technique, which has been used in many hydrological uncertainty studies (Sun et al, 2008;Zhang et al, 2016). The Monte Carlo technique is a type of random sampling method that considers combinations of different input components and determines a statistical distribution for the output data (Shen et al, 2013). A key step is sampling variables randomly for discrete data so that the measurement and prediction data can be expressed as certain distributions.…”
Section: The Mca Methodsmentioning
confidence: 99%
See 3 more Smart Citations